Being Assigned Work in Prison: Do Gender and Race Matter?. (October 2018) - Crittenden, Courtney A.; Koons-Witt, Barbara A.; Kaminski, Robert J.
With a majority of inmates being assigned some type of work while incarcerated, work assignments are a staple of U.S. prisons. These work assignments are likely to impact not only prisoner behavior while in prison, but also may impact their ability to obtain gainful employment after prison. Historically, it has been noted that work in prison has been influenced by gender and racial norms and stereotypes. These stereotypical assignments may not be beneficial for inmates, especially in a time when work assignments are increasingly providing the only work skills inmates may receive while incarcerated. Using a nationwide data set of prisoners incarcerated facilities, the current study uses multilevel modeling to examine the nature of work assignments for male and female state prisoners and whether these assignments are based on gender and/or racial stereotypes. Results indicate that there are indeed lingering stereotypes influencing work assignments for men and women in U.S. prisons.